2010
DOI: 10.1007/s10800-010-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nafion® ionomer on carbon corrosion

Abstract: Corrosion of the three carbon black materials which differ in their textural, sub-structural, and morphological characteristics is studied in H 2 SO 4 electrolyte at 80°C at positive polarization. Impregnation of carbon blacks with Nafion Ò ionomer is found to strongly affect their susceptibility to corrosion, which varies non-monotonically as a function of the Nafion Ò loading. Low temperature nitrogen adsorption is applied to study the distribution of the ionomer molecules in the carbon matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…A comparison of the three MEAs revealed that the fuel cell degradation rates were dependent on the electrode layer composition. The high catalyst and Nafion coating loadings likely provide a durable electrode structure because Nafion has been shown to prevent carbon corrosion [89]. The obtained data demonstrated a CO tolerance of the Fe/N/C cathodes, confirming previously published data where CO effects were studied using RDE techniques [29,30].…”
Section: Effect Of Co On a Fuel Cell Performancesupporting
confidence: 85%
“…A comparison of the three MEAs revealed that the fuel cell degradation rates were dependent on the electrode layer composition. The high catalyst and Nafion coating loadings likely provide a durable electrode structure because Nafion has been shown to prevent carbon corrosion [89]. The obtained data demonstrated a CO tolerance of the Fe/N/C cathodes, confirming previously published data where CO effects were studied using RDE techniques [29,30].…”
Section: Effect Of Co On a Fuel Cell Performancesupporting
confidence: 85%
“…However, Nafion® molecules are complex entities, which participate in a variety of interactions involving their polar (ether and sulfonic) and non-polar (perfluorinated backbone) groups. The previous papers [37,38,41] reported actual Nafion® quantities on the Vulcan surface in presence of ionomer's liquid solutions. To the contrary, the voltammetric technique used in our study ( Fig.…”
Section: The Effect Of Nafion On the Electrochemical Behavior Of Vulcmentioning
confidence: 99%
“…However, the ability of Nafion® to act as a surfactant indicates the existence of specific interactions between the catalyst/support particles and the ionomer. In fact, a strong monolayer Nafion® adsorption from liquid solutions on a variety of carbon supported Pt catalysts and catalyst supports has been demonstrated [37][38][39][40][41]. While the respective catalyst activities have not been reported [37][38][39][40], the voltammograms of carbon nanotube (CNT) supported Pt catalysts in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon specimen was suspended in 2 ml of isopropanol:water (3:2) mixture and sonicated in an ultrasonic bath for 15 min, then an aliquot of the Nafion® dispersion in water was added and the mixture was sonicated for another 15 min. Because the corrosion current densities obey inverted volcano‐like dependence on the amount of Nafion® with a minimum at ∼0.8 mg Nafion m −2carbon 16 in this work the corresponded quantity of Nafion® was added to suspension (∼0.8* A BET ). Samples were dried during 1.5 h in a furnace at 105 ± 1 °C and then mounted in the electrochemical cell.…”
Section: Experimental and Methodologymentioning
confidence: 99%